The Analysis of Self-Regulated Learning in Improving Speaking Skills at the Classroom Context - Eka Prabawati Rum; Markus Deli Girik Allo (Celebes Scholar pg, 2023)
This research aims to investigate how students self-regulated their learning in order to build their speaking abilities within the framework of a classroom setting. Since the majority of the study focuses on the relevance of speaking skills, this research is particularly relevant. This study examines how students may better themselves by self-regulating their learning to improve their speaking abilities in terms of smoothness or fluency in a classroom setting. In this particular study, the paradigm of quantitative research was used. The sample in this study was recruited from one of the junior high schools and totalled 33 students. The speaking test was the instrument used to gather the data. Based on the findings of the data, the students had a mean score of 71.66 on the pre-test assessment of their fluency (smoothness). While the post-test had a mean score that was higher than the pre-test, the post-test score for fluency was 81.06. Furthermore, the analysis of the data showed that the value of the t-test was more than the values in the t-test table (12.590 > 1.693). It indicated that there was a considerable disparity between them. Accordingly, it is possible to draw the conclusion that the implementation of Self-Regulated Learning was seen to be successful in improving the students' speaking abilities, particularly their fluency.